The mainstream of civilization - Strayer, Joseph R. (Joseph Reese) 1904-1987; Gatzke, Hans Wilhelm 1915- (San Diego, Calif. Harcourt Brace Jovanovich, 1984)
Traces the history of the world's major civilizations discussing their special characteristics and contributions.
Includes bibliographical references and index.
Keywords: Civilization -- History